Effect of Folic Acid and Vitamin B12 on Pemetrexed Antifolate Chemotherapy in Nutrient Lung Cancer Cells. (31st July 2013) - Yang, Tsung-Ying; Chang, Gee-Chen; Hsu, Shih-Lan; Huang, Yi-Rou; Chiu, Ling-Yen; Sheu, Gwo-Tarng
Abstract : Pemetrexed (MTA) is a multitargeted antifolate drug approved for lung cancer therapy. Clinically, supplementation with high doses of folic acid (FA) and vitamin B12 (VB12) lowers MTA cytotoxicities. An antagonistic effect of FA/VB12 on MTA efficacy has been proposed. However, patients who receive FA/VB12 show better tolerance to MTA with improved survival. The aims of this study are to investigate the modulation of FA and VB12 on MTA drug efficacy in human nonsmall cell lung cancer (NSCLC) cell lines. The sensitivities of cells, apoptosis, and MTA-regulated proteins were characterized to determine the possible effects of high doses of FA and VB12 on MTA efficacy. MTA has the lowest efficacy under 10% serum conditions. However, supplementation with FA and VB12 individually and additively reversed the insensitivity of NSCLC cells to MTA treatment with 10% serum. The enhanced sensitivities of cells following FA/VB12 treatment were correlated with increasing apoptosis and were specific to MTA but not to 5-fluorouracil (5-FU). Enhanced sensitivity was also associated with p21 WAF1/Cip1 expression level. Our results revealed no antagonistic effect of high doses of FA/VB12 on MTA efficacy in cancer cells grown in nutrient medium. Furthermore, these data may partially explain why supplementation of FA and VB12 resulted in better survival in MTA-treated patients.